Leadership and International Collaboration of Institutions Toward World Class Education - Fahrizal Nover; Kasful Anwar Us; Fridiyanto (Future Techno-Science, 2026)
In the era of globalization and increasing competition among higher education institutions, Universitas Negeri Jakarta (UNJ) is striving to achieve the status of a World Class Education (WCE) institution. This study aims to explore how leadership and international collaboration at both institutional and human resource levels contribute to the realization of WCE at UNJ. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews with university leaders, international office staff, and academic personnel, alongside analysis of institutional documents. The findings reveal that visionary, transformational, and distributed leadership plays a crucial role in fostering internationalization strategies, including academic mobility, global research partnerships, and cross-border curriculum development. However, the study also identifies significant challenges such as limited institutional synergy, inadequate international literacy among staff, and underdeveloped monitoring systems for sustainable collaboration. The research emphasizes the need for integrated leadership models and systematic human resource development to enhance global competitiveness. Ultimately, the synergy between effective leadership and strategic international cooperation is essential for positioning UNJ as a globally recognized university.